STUDY OF CRYSTAL MORPHOLOGIES OF HYDROGENATED CASTOR OIL AS A RHEOLOGY MODIFIER - Yang, Dingzheng (My University, 2012)
Hydrogenated castor oil (HCO) crystals as a rheology modifier have been widely used in paints, cosmetics and household products. In this thesis, we are interested in the effect of crystal morphology on the suspension rheology of products. Three major types of micron-sized crystal morphologies have been observed: fiber, rosette and irregular crystal. Fibers show a high aspect ratio with the length ranging from 5 to 33 µm and width around 1~3 µm. The rosette (2~50 µm) is a three-dimensional spherulitic structure with nano-fibrous arms extruding from a heterogeneous central point. Irregular crystals with equivalent diameter ranging from 4 to 84 µm are hard solid and show irregular shapes. There is an additional fourth type of crystal morphology which is a nano-sized fibrous structure that is assumed to be broken down from arms of micron-sized rosettes and fibers. Due to the relatively small amount, the effects of nano-fibrous fragments on rheology were not considered separately in this work.
The effect of temperature and shear history on the HCO crystal morphology has been studied. The energy barrier to nucleation for fibers is suggested to be higher than that of rosettes. Irregular crystals are thermodynamically less stable and tend to transform into stable polymorphs. A non-isothermal crystallization study showed that the formation of rosettes and fibers was favored by a slow cooling rate (1°C/min) while the formation of irregular crystals was favored by a fast cooling rate (5°C/min). Shear rates from zero to 100 s-1 have been applied at cooling rates from 1°C/min to 5°C/min. Nucleation has been found to be promoted with the increase of shear rate. Morphological analysis indicated that the formation of fibers was favored by gentle shear (e.g., 1 s-1), but fibers can be broken with the increase of shear time.
Kinetics of isothermal crystallization of hydrogenated castor oil in water emulsions exhibiting multiple crystal morphologies has been studied in the temperature range of 55°C to 70°C. The induction time of nucleation increases with the increase of the isothermal temperature under which crystallization occurred. A linear increase in induction time with increased temperature was found for both fibers and rosettes. A modified Avrami model was developed by introducing the volume fraction of each type of morphology into three dimensional and one dimensional full Avrami models. It was found that the experimental trends for mixed crystal morphologies could be captured by the modified Avrami model.
Due to the difficulty of obtaining samples with a single crystal morphology, rheological studies of suspensions containing mixtures of the three morphologies in a surfactant solution have been undertaken. The viscometry of dilute suspensions has shown that the magnitude of intrinsic viscosity is dominated by the fraction of a crystal morphology type, i.e. fiber > rosette > irregular crystal. A modified Farris model was fitted to the rheology data from mixtures of crystal morphology with interacting particles. A yield stress exists for concentrated suspensions followed by a shear thinning behavior with the increase of shear rate. A power-law relation has been found between yield stress and total particle volume fraction with a constant exponent of 1.5 regardless of crystal morphology.
Keywords: morphology; rheology; hydrogenated castor oil; crystallization; emulsion; suspension; Complex Fluids; Complex Fluids